Thermal stability under laser heating of hot-pressed (Hf1-X ZrX)B2/SiC powder mixtures obtained by mechano-synthesis. Issue 15 (December 2019) - Monteverde, F.; Cordoba, J.M.; Savino, R.; Cecere, A.; Genna, S.; Leone, C.
Abstract: The paper studied ultra-refractory (Hf1-X ZrX )B2 /SiC ceramics fabricated by hot-pressing (HP) of mechano-chemically assisted precursors synthesis, and tested their thermal stability under laser heating. Fully dense materials were obtained after HP. Microstructures of the sintered materials were analyzed by XRD and SEM-EDS, while 4-pt flexure strength in air at room temperature up to 1773 K was measured. The thermal stability was tested using a diode laser source. A SiC-free fully dense ZrB2 ceramic was used as benchmark to identify the potential of the laser heating technique and separate the effects related to the addition of SiC into a diboride ceramic matrix. Infrared thermo-camera and 2-color pyrometer provided the real-time variation of the surface temperature vs time. For surface temperatures below 1900 K reached by the SiC-containing samples, SiC acted as a key player and provided excellent protection to the diboride matrices against oxidation: extensive post-test microstructural analyses documented this response.